Activation of GABAA Receptors by Guanidinoacetate: A Novel Pathophysiological Mechanism - Axel Neu; Henrike Neuhoff; Gerhard Trube; Susanne Fehr; Kurt Ullrich; Jochen Roeper; Dirk Isbrandt (Neurobiology of Disease, 2002)
Guanidinoacetate methyltransferase (GAMT) deficiency is an autosomal recessively inherited disorder of creatine biosynthesis. The disease occurs in early life with developmental delay or arrest and several neurological symptoms, e.g., seizures and dyskinesia. Both the deficiency of high-energy phosphates in neurons and the neurotoxic action of the accumulated metabolite guanidinoacetate (GAA) are candidate mechanisms for the pathophysiology of this disease. To examine a potential role of GAA accumulation, we analyzed the electrophysiological responses of neurons induced by GAA application in primary culture and acute murine brain slices. GAA evoked picrotoxin- and bicuculline-sensitive GABAA receptor-mediated chloride currents with an EC50 of 167 μM in cortical neurons. Pathophysiologically relevant GAA concentrations hyperpolarized globus pallidus neurons and reduced their spontaneous spike frequency with an EC50 of 15.1 μM. Furthermore, GAA acted as a partial agonist at heterologously expressed GABAA but not GABAB receptors. The interaction of GAA with neuronal GABAA receptors represents a candidate mechanism explaining neurological dysfunction in GAMT deficiency.